2018
DOI: 10.1007/s00464-018-6177-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety and curability of laparoscopic gastrectomy in elderly patients with gastric cancer

Abstract: Laparoscopic gastrectomy for gastric cancer could be safely performed in elderly patients with acceptable postoperative morbidity and curability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 27 publications
5
21
0
Order By: Relevance
“…However, previous studies on the long-term outcomes of laparoscopic gastrectomy have reported that OS in an elderly group was poorer than that in non-elderly groups and that the DSS rates of the two groups were equivalent. In these studies, it was concluded that other causes of death affected OS in elderly patients (4)(5)(6)17). This study was compatible to previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…However, previous studies on the long-term outcomes of laparoscopic gastrectomy have reported that OS in an elderly group was poorer than that in non-elderly groups and that the DSS rates of the two groups were equivalent. In these studies, it was concluded that other causes of death affected OS in elderly patients (4)(5)(6)17). This study was compatible to previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, multivariate analysis showed that extended operation time was an independent risk factor for the occurrence of severe complications in the elderly group. Additionally, LG was not identified as a risk factor for overall and severe complications, which is similar to the previous studies comparing the clinical outcomes of LG and OG for elderly gastric-cancer patients [ 20 , 38 ].…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the effect of survival in elderly patients, Zheng et al [ 41 ] reported similar 2-year OS rates between the LG and OG groups. Shimada et al [ 20 ] demonstrated that LG could be a curative therapy procedure for elderly gastric-cancer patients in the comparison of 5-year DSS rates between elderly and non-elderly groups. In the current study, the 5-year OS rate of patients in the ELG group was lower than that in the NLG group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason is the higher prevalence of cardiac, pulmonary and other comorbidities in older patients [8,9]. Although some surgeons suggest that less invasive surgery, such as laparoscopic surgery, is of greater benefit in elderly patients [10][11][12], our previous survey on gastric cancer surgery using a national clinical database (NCD) have shown that surgeons tend to select open surgery for elderly patients [13][14][15][16]. Several clinical trials have demonstrated that the surgical outcomes of laparoscopic gastrectomy (LG) are similar or superior to those of open gastrectomy (OG) for patients with gastric cancer [17][18][19][20][21]; however, there is still little evidence of the efficacy and safety in elderly patients in routine clinical practice [22][23][24].…”
Section: Introductionmentioning
confidence: 99%